Efektivitas Penggunaan Model Alat Respirasi dalam Menjelaskan Bahaya Rokok Kepada Siswa Kelas IX SMP Negeri 13 Banda Aceh - Abdullah Abdullah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
The study on "Effectiveness in the Use of Respiratory Equipment Model Describes Dangers Of Smoking on Respiratory System Student Class IX SMP Negeri 13 Banda Aceh, was held on January 23, 2010. This study aims to determine the effectiveness of the use of respiratory equipment models in explaining the dangers of smoking on the students. Subjects in this study were the students who smoked in the Class IX students numbering 50 people. The method used in this study is an experiment in "Pre-test and post-test." Data were analyzed with statistical t-test formula. Results of data analysis obtained t = 13.1 (α = 0.05; db = 49) obtained t table price = 2.01, which is well known t t table. Thus, it can be concluded that the knowledge given to students about the dangers of cigarettes and content by using the modeling tools can improve students' knowledge of Class IX SMP Negeri 13 Banda Aceh on the respiratory system and knowledge about the dangers of cigarettes.